Leadership, Work Motivation, Competency, Commitment and Culture: Which influences The Performance of Quality Management System in Automotive Industry? - Praditya, Rayyan Aqila (Journal of Industrial Engineering & Management Research, 2020)
The purpose of this study is to analyze the influence of leadership, motivation, competence, commitment, and organizational culture on the implementation performance of the ISO 9001 2015 quality management system at PT.AGP is one of automotive industry located in Tangerang. The study population is all 63 employees of PT. AGP. The sampling technique used is simple random sampling by randomly drawing employees' numbers. The number of samples calculated using the Slovin formula is 63 people. The analysis of this study uses SEM (Structural Equation Model) with the SmartPLS software program version 3.0. The results show that leadership, commitment, and organizational culture have a positive and significant influence on the implementation performance of the ISO 9001 2015 quality management system, while competence and motivation do not affect the implementation performance of the ISO 9001 2015 quality management system